2014
DOI: 10.1128/aac.02311-13
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Cyclopropavir and Ganciclovir in Human Cytomegalovirus-Infected Cells

Abstract: H uman cytomegalovirus (HCMV) is a widespread pathogen infecting between 40% and 80% of the population worldwide (1). Although individuals with competent immune systems rarely manifest any symptoms, HCMV infections can result in severe interstitial pneumonia, encephalitis, and gastroenteritis in immunocompromised individuals (2). HCMV is also the most common congenital infection in the United States and results in over 4,000 cases of severe mental disabilities, hearing, and/or vision loss in infants each year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Some of this increased potency may be due to greater accumulation in infected cells of CPV-TP than GCV-TP at equivalently effective concentrations, which is consistent with more extensive phosphorylation of CPV than GCV by UL97 (6,11). However, CPV is also more potent than GCV against HCMV lacking UL97 (3, 9, 13).…”
supporting
confidence: 48%
See 4 more Smart Citations
“…Some of this increased potency may be due to greater accumulation in infected cells of CPV-TP than GCV-TP at equivalently effective concentrations, which is consistent with more extensive phosphorylation of CPV than GCV by UL97 (6,11). However, CPV is also more potent than GCV against HCMV lacking UL97 (3, 9, 13).…”
supporting
confidence: 48%
“…Previous work had established that CPV is phosphorylated to CPV-TP in HCMV-infected cells (11), that CPV inhibits HCMV DNA synthesis (3), and that mutations in the HCMV pol gene can confer CPV resistance (12). These results suggested that CPV-TP targets HCMV Pol to block viral DNA synthesis, but the action of CPV-TP on HCMV Pol had not been explored.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations